Collaborative Knowledge Management Through Product Lifecycle A Computational Perspective - Wang, Hongwei; Peng, Gongzhuang (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book not only presents the state-of-the-art research on knowledge modelling, knowledge retrieval and knowledge reuse, but also elaborates the Collaborative Knowledge Management (CKM) paradigm and the architecture for the next generation of knowledge management systems. Although knowledge management has been extensively studied, particularly in the fields of business management and engineering design, there is a lack of systematic methodologies for addressing the integrated and collaborative dimension of knowledge management during the collaborative process of designing and developing complex systems, products, processes and services. The rapid development of information technologies, together with their applications in engineering and management, has laid the foundation for a Collaborative Knowledge Management (CKM) paradigm. The book specifically discusses this paradigm from a computational perspective. By exploring specific research findings underpinning further CKM research and applications and describing methods related to hot research topics and new research areas, the book appeals to professionals, researchers and graduate students who are interested in knowledge management and related topics and who have a basic understanding of information technologies, computational methods, and knowledge management.
Knowledge management through product lifecycle -- The collaborative knowledge management paradigm -- Knowledge modelling methods -- Advanced knowledge retrieval methods -- Knowledge reuse in collaborative knowledge management -- Discussion.
Keywords: Computer-aided engineering; Engineering design; Electronic data processing -- Management; Application software; Information storage and retrieval systems; Computer systems; Computer-Aided Engineering (CAD, CAE) and Design; Engineering Design; IT Operations; Computer and Information Systems Applications; Information Storage and Retrieval; Computer System Implementation